Proactive Evaluation of an Operating Room Prototype: A Simulation-Based Modeling Approach. Issue 8 (December 2021) - Taaffe, Kevin; Joseph, Anjali; Khoshkenar, Amin; Machry, Herminia; Allison, David; Reeves, Scott T.; ,
Abstract : Objectives: There is a pressing need to improve safety and efficiency in the operating room (OR). Postsurgical adverse events, such as surgical site infections and surgical flow disruption, occur at a significant rate in industrial countries where a considerable portion of such complications result in death. The aim of the study was to identify an ideal room design that improves the flow of staff members using risk and safety performance measures. Methods: Operating room designs were compared by using computer simulation modeling to analyze traffic flow inside an OR. The study was conducted in two phases. A historical data set was first created based on surgical flow data obtained from 23 video observations of actual surgical procedures. A detailed simulation-based model was then developed. Results: As room size increases, staff members have more available space to maneuver in the room, resulting in more distance walked but far fewer undesirable contacts. An angled table orientation is preferred with the circulating nurse workstation at the foot of the OR table, as it provides more space for staff to move across the room without increasing the number of contacts. Furthermore, when the nurse workstation is near the wall, staff members experience fewer undesirable contacts. Conclusions: Simulation modeling was used to assess the impact of OR layout alternatives on three performance metrics, and the medium-sized OR prototype performs well across the metrics. Future research will consider the relative influence of several factors on traffic-based safety and efficiency performance metrics, resulting in a more predictive simulation design model.